2023
DOI: 10.3390/su15075775
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Heterogeneity of Rural Habitat Level Evolution and Its Influencing Factors—A Case Study of Rural Villages in Nature a Reserve of China

Abstract: Taking China’s Qilian Mountains Nature Reserve as an example, entropy, hierarchical analysis and spatial autocorrelation analysis methods were combined with geographically and temporally weighted regression to construct an evaluation index system of a rural habitat environment. The spatiotemporal characteristics of the evolution of the rural habitat environment in the Qilian Mountains Nature Reserve from 2000 to 2020 were revealed, and the spatiotemporal heterogeneity of factors affecting the evolution of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
2
2
0
Order By: Relevance
“…Based on the test results in the first and second steps, the third step explores whether the policy indirectly promotes ecological improvement at the scale of agricultural production per unit of land and government tax revenue. The estimation results of models ( 5) and (6) show that the selected mediating variables are all partially mediated, and both are consistent with theoretical expectations. The negative lntax coefficients in model ( 6) may be because the ecological treatment policy closes some higher-polluting enterprises, or the local government provides tax relief for the transformation of high-polluting enterprises, resulting in a decline in local tax revenue in the short term.…”
Section: Ecological Governance Policy Mechanism Testsupporting
confidence: 83%
See 2 more Smart Citations
“…Based on the test results in the first and second steps, the third step explores whether the policy indirectly promotes ecological improvement at the scale of agricultural production per unit of land and government tax revenue. The estimation results of models ( 5) and (6) show that the selected mediating variables are all partially mediated, and both are consistent with theoretical expectations. The negative lntax coefficients in model ( 6) may be because the ecological treatment policy closes some higher-polluting enterprises, or the local government provides tax relief for the transformation of high-polluting enterprises, resulting in a decline in local tax revenue in the short term.…”
Section: Ecological Governance Policy Mechanism Testsupporting
confidence: 83%
“…The regression results of model (5) show that the coefficient of the interaction term (DID × gspend) is significantly positive, indicating that the degree of municipal government intervention in the economy can directly affect urban residents; i.e., the ecological governance policy directly improves the business environment and rationalizes the economic structure of the city, and urban residents are the direct beneficiaries. The regression results of model (6) show that the coefficient of the interaction term (DID × gspend) is positive and insignificant, verifying the conclusions of models ( 3) and ( 4): the higher the degree of municipal government intervention in the economy, the less effective the policy implementation in ecological governance at the village level. Regarding the policy spillover effect, it can be observed in model (7) of Table 5 that the coefficient of DID is positive at the 10% significance level and is relatively small at 5.4% from the economic significance level, indicating that there is a significant but not a strong positive spillover effect from the policy.…”
Section: Heterogeneity and Spillover Effects Testsupporting
confidence: 64%
See 1 more Smart Citation
“…Due to the unique mountainous terrain, the ecosystems of rural settlements are relatively fragile, making them more susceptible to external disturbances and degradation. Wang, Y. et al point out that spatial planning for mountainous rural settlements plays a critical role in ensuring the harmonious development of mountain ecosystems and human activities [106]. Liu, L. et al found that cultivated land, grassland, and forest are the primary influencing factors in the evolution of rural settlements, and the interactions between mountainous and aquatic environments, aquatic facilities, agricultural production, and cultural heritage collectively shape the living environment of mountainous rural settlements [28].…”
Section: Ecological Conservation and Fosteringmentioning
confidence: 99%